The comparison of muscle length and strength of lower extremity in athletes with and without patellofemoral pain syndrome - Mousavi, L. S.; Norasteh, A. A. (Medicina dello Sport, 2011)
Aim. Development of patellofemoral pain syndrome is considered multifactorial. Muscle tightness or shortness and muscle strength is challengeable issue in athlete with patellofemoral pain syndrome. The aim of this study was to investigate the muscle length and strength of lower extremity in athletes with and without patellofemoral pain syndrome.